The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5812/amh.112274
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Advantages of Nano-based Drug Delivery Systems

Abstract: Context: During the past two decades, the development of drug delivery systems based on nanomaterials has yielded nanocarriers for smart application in nanomedicine to treat diseases. Evidence Acquisition: The current review presents a summary of some advances in the development and application of nano-delivery systems for improving the efficacy of conventional drugs and reducing their adverse effects through the production of smart delivery carriers with targeting moieties and controlled release strategies us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…[9,10] Within this overarching context, nanotechnology has materialized as a propitious enabler in the field of drug delivery, as evidenced by a surge in investigations related to nano-drug delivery systems (NDDSs). [11] NDDSs, owing to their nanoscale proportions, boast heightened biocompatibility, augmented bioavailability, and the ability to target drug delivery [13,14] precisely. The incorporation of nanoparticles into nanocomposites often serves to enhance the aqueous solubility of poorly soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Within this overarching context, nanotechnology has materialized as a propitious enabler in the field of drug delivery, as evidenced by a surge in investigations related to nano-drug delivery systems (NDDSs). [11] NDDSs, owing to their nanoscale proportions, boast heightened biocompatibility, augmented bioavailability, and the ability to target drug delivery [13,14] precisely. The incorporation of nanoparticles into nanocomposites often serves to enhance the aqueous solubility of poorly soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have small sizes that vary between 1 and 100 nm, and high surface area to volume ratio. Therefore, nano-based drug delivery systems provide better absorption, bioavailability and stability than other known drug delivery systems [15]. Selenium nanoparticles are a subject of interest in nanomedicine for multiple reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] NP-based drug delivery systems (DDSs) have several advantages compared to traditional methods of administering therapeutic agents. [6] Despite DOI: 10.1002/smll.202305375 the widespread use of drugs as a treatment for diseases, clinical trials have shown limited efficacy due to low accumulation in target cells, rapid clearance, and the potential for adverse reactions due to supplement overdose. [7,8] The utilization of NPs can improve the pharmacological properties of small-molecule drugs, including increasing aqueous solubility, improved bioavailability, and reducing adverse side effects.…”
Section: Introductionmentioning
confidence: 99%